Assessing the spatial–temporal response of groundwater‐fed anchialine ecosystems to sea‐level rise for coastal zone management. Issue 4 (3rd February 2021) - Marrack, Lisa; Wiggins, Chad; Marra, John J.; Genz, Ayesha; Most, Rebecca; Falinski, Kim; Conklin, Eric
Abstract: As a result of sea‐level rise (SLR), coastal anchialine pool habitats will be lost in some locations and will expand inland into low‐lying areas in others. New and existing habitats may risk additional SLR‐related degradation from non‐native species transmission, groundwater pollution, and increased contact with human infrastructure. Despite a worldwide distribution, anchialine ecosystems and biota have been largely omitted from SLR risk assessments for coastal ecosystems. Anchialine pools and caves are composed of brackish groundwater that connects to the marine environment through porous rocky substrate but have no overland connection to the ocean. They support unique endemic biota. The goal of this study was to develop methods to assess potential impacts to anchialine pools from future coastal flooding, using the island of Hawai'i as a case study. Flood predictions incorporated pool surveys, groundwater‐level measurements, and statistical analysis of flood frequencies observed in tide gauges combined with regional scenario‐based projections of future sea levels. High‐resolution geospatial models were then generated to predict anchialine pool location, density, and risk factors for the next 60 years. Along 40 km of coastline, up to 80% of current anchialine pools will be lost by 2080 as pools merge with ocean habitats; however, as groundwater flooding occurs more frequently and new habitats are created inland, the total pool counts will rise from 509 in 2018 to 1, 000 by 2080. As a result of extreme water‐level events, non‐native fishes are predicted to disperse into 42% of pools by 2030. Based on current conditions, development and cesspool risks are quite low for anchialine pools in the study area. Outcomes from this study are guiding conservation actions, including habitat restoration, non‐native fish removal, and development planning decisions in coastal areas. This study illustrates methods that can be used to assess the effects of SLR on anchialine pool habitats worldwide.